Pengaruh Kinerja Keuangan Terhadap Pertumbuhan Laba Pada Perusahaan Manufaktur Yang Terdaftar Dibursa Efek Indonesia - Nur Eliza Afriyanti; Dewi Ayu Wulandari (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2023)
This research is aimed to analyze the effect of Liquidity, Activity, solvency and profitability on profit growth in manufacturing companies listed on the Indonesia Stock Exchange for the 2017-2021 period. The data analysis method used is multiple linear regression method. This research uses secondary research by taking the samples used in this study are manufacturing companies listed on the Indonesia Stock Exchange for the 2017-2021 period. By using a purposive sampling technique, 46 companies met the criteria in this study. The data analysis technique used is multiple linear regression analysis. The results of this study indicate that the variable liquidity (CR) has no significant effect on firm value profit growth, Activity (TATO) has no significant effect on profit growth, Solvency (DAR) has a significant negative effect on profit growth, and profitability (ROE) has a significant positive effect on profit growth. Keywords: Liquidity (CR), Activity (TATO), Solvency (DAR), Profitability (ROE), profit growth.